Sveriges handelsvägar för tomat och äpple - Ahnström, Ellinor (2005)
The market of fruit and vegetables develops continuously to become tougher and more complex. The fast development makes it difficult to keep up with all the changes. This is the case for apples and tomatoes. The purpose of this work is to explain what the trade routes are like for Swedish imports as well as the Swedish production of tomatoes and apples, both in the present and the past times. There is also an ambition to create comprehension of the trade routes. In the search of data for the work a period of collection, processing of statistic information and literature studies was initiated. This led to an explanation of why the trade routes are the way they are. Hence the qualitative study was started. Interviews were made with first and second level wholesalers, retailers and producer organisations. In order to create a picture as comprehensive as possible, interviews were chosen with the main actors on the market. The first level wholesalers are the ones that distribute the imports to the retailers. Since all the interviewed first level wholesalers are big on the Swedish market, they have a great impact on the trade in Sweden. It appeared that the distribution of their products differed from each other. Distribution to the grocery stores through terminals and imports directly of tomatoes and apples to the retailers are some examples. What is it that makes some companies successful on the Swedish market, in getting their products sold, and others not? One of the interviewees said that an actor on the market saying, "success depends on presenting Swedish products" would not be the successful. Instead, the one who says, "I have good products" will survive on the market. One part of this paper explains the work of strengthening the competitiveness of Swedish products and the influence of different actors on the Swedish trade. In order to reach this, the producer organisations in Sweden are working in cooperation and, among other things, work is done to bring together the Swedish supply and compete with the imports. In interviews with the first level wholesalers and the retailers it appears that they reason in different ways when they consider what is most important to their purchase. Both value quality high, while the demand is more important to the first level wholesalers than it is to the retailers. In same way the retailers value the price much higher. Statistical studies show that Swedish trade partners of tomatoes are within Europe, while the sources of apples are also found at longer distances. Those countries that have a season that corresponds with a period of needs of imports, can more easily establish themselves as new supply countries on the market. The seasonal variation contributes to natural variations of the source of imports on the Swedish market.